Kajian meta-analisis pengaruh metode penyembelihan terhadap kualitas daging ruminansia - Yuli Maulidiyah; Feri Kusnandar; Hanifah Nuryani Lioe; Anuraga Jayanegara (AGROINTEK, 2025)
Meats of consumable livestock for humans are commonly from ruminants, such as cows, goats, lambs, buffaloes, etc. The method of slaughtering the livestock at the slaughterhouse mostly applies non-stunning or stunning methods. The stunning method uses electricity, mechanics, and gas. The slaughtering methods influence the meat quality and results. Thus, further meta-analysis is important to provide valid and informative conclusions based on comprehensive investigations about the slaughtering method's effect on ruminant meat quality. The researchers applied the PRISMA diagram and the size of the Standard Mean Difference effect, SMD, with Hedge's formulation as the quantitative synthetical meta-analysis method. The results found that the slaughtering method with stunning and non-stunning methods did not significantly influence some parameters, such as pH, colors (L*, a*, and b*), the water holding capacity, cooking loss, and shear force. However, the methods significantly influenced the drip loss and myofibril fragmentation index parameters with SMD values 0.2, p-values 0.001 to 0.777, and heterogeneity values of 0% to 82.98%.